Genomic Copy Number Variants in CML Patients With the Philadelphia Chromosome (Ph+): An Update - Zhang, Heyang; Liu, Meng; Wang, Xiaoxue; Ren, Yuan; Kim, Young Mi; Wang, Xianfu; Lu, Xianglan; Pang, Hui; Liu, Guangming; Gu, Yue; Sun, Mingran; Shi, Yunpeng; et al. (Frontiers in Genetics, 2021)
Background: Submicroscopic segmental imbalances detected by array-comparative genomic hybridization (array-CGH) were discovered to be common in CML patients with t(9;22) as the sole chromosomal anomaly. To confirm the findings of the previous study and expand the investigation, additional CML patients with t(9;22) as the sole chromosomal anomaly were recruited and copy number variants (CNVs) were searched for. Methods: Karyotyping tests were performed on 106 CML patients during Jan 2010-Sep 2019 in our Genetics Laboratory. Eighty-four patients had the Philadelphia chromosome as the sole chromosomal anomaly. Only 49 of these 84 patients had sufficient marrow or leukemia blood materials to additionally be included in the array-CGH analysis. Fluorescence in situ hybridization (FISH) was carried out to confirm the genes covered by the deleted or duplicated regions of the CNVs. Results: 11 out of the 49 patients were found to have one to three somatic segmental somatic segmental (CNVs), including fourteen deletions and three duplications. The common region associated with deletions was on 9q33.3-34.12. Identified in five of the 11 positive patients with segmental CNVs, the deletions ranged from 106 kb to 4.1 Mb in size. Two cases had a deletion in the ABL1-BCR fusion gene on der (9), while three cases had a deletion in the ASS1 gene. The remaining CNVs were randomly distributed on different autosomes. Conclusion: Subtle genomic CNVs are relatively common in CML patients without cytogenetically visible additional chromosomal aberrations. Long-term studies investigating the potential impact on patient prognosis and treatment outcome is underway.